Visual culture and the Holocaust - Zelizer, Barbie 1954- Hrsg (Rutgers depth of field series, 2001)
Introduction : On visualizing the Holocaust / Barbie Zelizer -- In plain sight / Liliane Weissberg -- Of mice and mimesis : reading Spiegelman with Adorno / Andreas Huyssen -- Deadly historians : Boltanski's intervention in Holocaust historiography / Ernst van Alphen -- Lost in translation : Clement Greenberg, Anselm Kiefer, and the subject of history / Lisa Saltzman -- The man in the glass box : watching the Eichmann trial on American television / Jeffrey Shandler -- Tele-suffering and testimony in the dot com era / Geoffrey Hartman -- Schindler's list is not shoah : second commandment, popular modernism, and public memory / Miriam Bratu Hansen -- Hybrid victims : second-generation Israelis screen the Holocaust / Yosefa Loshitzky -- Daniel Libeskind's Jewish museum in Berlin : the uncanny arts of memorial architecture / James E. Young -- "From shore to shore" : the Holocaust, clandestine immigration, and Israeli heritage museums / Tamar Katriel -- Surviving images : Holocaust photographs and the work of postmemory / Marianne Hirsch -- Gender and atrocity : women in Holocaust photographs / Barbie Zelizer -- The shrunken head of Buchenwald : icons of atrocity at Nuremberg / Lawrence Douglas -- The tattooed Jew / Dora Apel -- Clicking on Hitler : the virtual Holocaust @home / Anna Reading -- Analogs of loss : Vera Frenkel's Body missing (http://www.yorku.ca/BodyMissing) / Elizabeth Legge